2021
DOI: 10.3390/su13158551
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Harmonic Emission of Electric Vehicles and Their Impact on Low Voltage Residential Network

Abstract: The EV penetration in the low voltage residential grids is expected to increase rapidly in the coming years. It is expected that EV consumers will prefer overnight home charging because of its convenience and lack of charging infrastructure. The EV battery chargers are nonlinear loads and likely to increase the current harmonic emission in the distribution network. The imminent increase of EV load requires upgrading or managing the existing power system to support the additional charging load. This paper provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A significant compensation with external load (heat pump) is reported in [70], where the constant increase of the 7th harmonic intensity is effectively reduced by the switching on of a heat pump; when the second heat pump is switched on overcompensation occurs and the contribution of the latter prevails; the observed EVs had a negligible contribution of 5th harmonic, so that the switching on of the first heat pump does not produce any beneficial effect. Iqbal et al [71] report a low variability of EV harmonic phase displacement for the 5th and 7th harmonics, spreading at most 45 • for the vast majority of the examined EVs (80% of a set of 11 EVs), preventing thus a substantial compensation between different EVs. In addition, it is observed that when comparing the harmonic phase angles of [70,71], they could be in agreement by applying a sign reversal, which raises a concern that many studies do not indicate clearly the polarity of the measured voltage and current quantities (e.g., voltage sign reversal as in German notation, preference for incoming or outgoing current).…”
Section: Discussion Of Publications and Experimental Datamentioning
confidence: 98%
See 1 more Smart Citation
“…A significant compensation with external load (heat pump) is reported in [70], where the constant increase of the 7th harmonic intensity is effectively reduced by the switching on of a heat pump; when the second heat pump is switched on overcompensation occurs and the contribution of the latter prevails; the observed EVs had a negligible contribution of 5th harmonic, so that the switching on of the first heat pump does not produce any beneficial effect. Iqbal et al [71] report a low variability of EV harmonic phase displacement for the 5th and 7th harmonics, spreading at most 45 • for the vast majority of the examined EVs (80% of a set of 11 EVs), preventing thus a substantial compensation between different EVs. In addition, it is observed that when comparing the harmonic phase angles of [70,71], they could be in agreement by applying a sign reversal, which raises a concern that many studies do not indicate clearly the polarity of the measured voltage and current quantities (e.g., voltage sign reversal as in German notation, preference for incoming or outgoing current).…”
Section: Discussion Of Publications and Experimental Datamentioning
confidence: 98%
“…Iqbal et al [71] report a low variability of EV harmonic phase displacement for the 5th and 7th harmonics, spreading at most 45 • for the vast majority of the examined EVs (80% of a set of 11 EVs), preventing thus a substantial compensation between different EVs. In addition, it is observed that when comparing the harmonic phase angles of [70,71], they could be in agreement by applying a sign reversal, which raises a concern that many studies do not indicate clearly the polarity of the measured voltage and current quantities (e.g., voltage sign reversal as in German notation, preference for incoming or outgoing current).…”
Section: Discussion Of Publications and Experimental Datamentioning
confidence: 98%
“…The harmonic cancellation refers to the cumulation of the harmonic currents in such a manner that the resulting RMS harmonic current is lower than the arithmetic sum [26][27][28]. The cases with arithmetic sum (in case only RMS measurements are available) and geometric sum (RMS and phase angle data are available) is presented here.…”
Section: Aggregation Analysis and Harmonic Cancellation Estimationmentioning
confidence: 99%
“…The resulting harmonic levels are decreased due to the cancellation effect, and high-order harmonics have more average reduction as compared to lower-harmonic orders. The harmonic cancellation refers to the cumulation of the harmonic currents in such a manner that the resulting RMS harmonic current is lower than the arithmetic sum [26][27][28]. The cases with arithmetic sum (in case only RMS measurements are available) and geometric sum (RMS and phase angle data are available) is presented here.…”
Section: Aggregation Analysis and Harmonic Cancellation Estimationmentioning
confidence: 99%
“…Sustainable electrical grids of the future include EVs as an essential part of consuming and producing electricity to the grid. Therefore, the current SI further includes the impact of the EVs on low voltage residential networks, as well as more deep studies on electrical grid power quality issues, also by Iqbal et al [9].…”
mentioning
confidence: 99%